Territorial dynamics of innovation: Perspectives of institutional economists and evolutionists - Rodrigues, Ricardo Furtado (Seven Editora, 2024)
This chapter discusses the importance of the territory as a space for innovation. And to better understand the situation studied, it was necessary to discuss the view of institutionalist and evolutionist economists who will form the basis for understanding the main institutional aspects that can influence the performance of companies, and the materialization of an institutional environment favorable to innovation, through interaction in formal and informal knowledge networks. It highlights the importance of knowledge as a central element of a new territorial economic structure that is emerging, where learning is its most important process, and innovation is the main vehicle for transforming knowledge into value. The chapter also presents the main concepts of Innovation Systems, making reference to the main authors, and finally, a discussion on the formation of business networks and the importance of cooperation between actors. DOI:https://doi.org/10.56238/sevened2024.007-038